The Bioavailability and Pharmacokinetics of Silymarin SMEDDS Formulation Study in Healthy Thai Volunteers - Chuleegone Sornsuvit (2018)
© 2018 Chuleegone Sornsuvit et al. The present study aimed to determine the pharmacokinetic parameters and bioavailability of silymarin 140 mg SMEDDS formulation. An open-label, single-dose pharmacokinetic study was conducted. Twelve healthy volunteers were included in the study. After the volunteers had fasted overnight for 10 h, a single-dose generic silymarin 140 mg SMEDDS soft capsule was administered. Then 10 ml blood samples were taken at 0.0, 0.25, 0.50, 0.75, 1.0, 1.33, 1.67, 2.0, 2.5, 3.0, 4.0, 6.0, 8.0, 10.0, and 12.0 h. The plasma silybin concentrations were analyzed using validated LC-MS/MS. The pharmacokinetic parameters were analyzed and calculated. The pharmacokinetic parameters were calculated after silymarin had been administered as a single capsule. The mean (range) Cmaxwas 812.43 (259.47-1505.47) ng/ml at 0.80 (0.25-1.67) h (tmax). The mean (range) AUC0-tand AUC0-infwere 658.80 (268.29-1045.01) ng.h/ml and 676.98 (274.10-1050.96) ng.h/ml, respectively. The mean keand t1/2were 0.5386 h-1and 1.91 h, respectively. The silymarin SMEDDS formulation soft capsule showed rapid absorption and high oral bioavailability.